Effects of Debris Flows on Channel Morphology at Jiangjia Ravine, Yunnan Province, China - zhu, Xing-hua; cui, Peng; zhang, Jin-shan (Italian journal of engineering geology and environment, 2011)
Debris flows, widespread in mountainous areas of China, transport large amounts of sediment in small intervals of time. To investigate the effects of debris flows on channel morphology, we chose 10 cross-sections to monitor periodic series of multiple debris flows triggered by summer rainstorms at Jiangjia ravine, Yunnan province, southwestern China. The 10 sections were distributed in the upper, middle, and lower sections of the trunk drainage to record erosion and deposition. Based on the observation data from 1999 to 2006, the effects of debris flows on channel morphology in the upper, middle and lower channel were analyzed respectively. It can be found that the channel morphology evolvement in upper, middle and lower channel were not uniform, as the erosion or deposition of a specific section depends on the local conditions of the section and scale of the debris flow. The analysis shows sediment discharge, maximum velocity of debris flow and channel gradient are three key factors in erosion/deposition volume calculation in channel. Based on the erosion/deposition characters of Jiangjia ravine, a simple computational model is presented to calculate the erosion or deposition of the debris flow channel.